Sistem Pakar Diagnosis Penyakit Ayam Broiler Berbasis Web - Riduan Syahri; Debi Gusmaliza; Risnaini Masdalipa (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
Mr. Jumaldi Jani, SP., MM Broiler Chicken Farm is a chicken farm that was founded in 2013. In carrying out its business processes, handling of raising and developing poultry is only handled by one person who is taken as the farm supervisor. This is very ineffective in handling diseases that attack chickens because the knowledge of the maintenance and handling of chickens that have disease is only owned by one person. The purpose of this study is to create a Web-Based Chicken Disease Diagnosis Expert System, which can be accessed easily, quickly, economically, can be done anytime or anywhere without knowing the distance and time. The method used in this research is web engineering which has stages: customer communication, planning, modeling, construction and deployment. The establishment of a Web-Based Broiler Chicken Disease Diagnosis Expert System is expected to facilitate the public about conducting consultations on Broiler chicken disease easily, quickly, and economically, it can be done anytime and anywhere without looking for distance and time.